Simultaneous Spectrophotometric Estimation of Ciprofloxacin and Tinidazole in Tablets Using Orthogonal Polynomial Function Method - KANNAPPAN, N.; KANNAN, K.; MANAVALAN, R. (Asian Journal of Chemistry, 2010)
A simple, accurate and reproducible spectrophotometric method, requiring no prior separation, has been developed for simultaneous estimation of ciprofloxacin and tinidazole in combined tablet dosage form. The described method was applied for the determination of these combinations in synthetic mixtures and tablet dosage forms. Contents in the tablets were found to be 100.56 ± 1.50 for ciprofloxacin and 99.16 ± 1.05 for tinidazole of the label claim. The linearity was validated by least square method. The recovery was with in the limit of 98 to 102 %. The proposed method is simple, economical, accurate, reproducible and rapid.